Determinants of menstrual hygiene among the adolescent girls in a South Indian village - Budimelli, Swapna; Chebrolu, Kalyan (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescent girls constitute a vulnerable group, particularly in India where female child is neglected one. Menstruation is still regarded as something unclean or dirty in Indian society. Although menstruation is a natural process, it is linked with several misconceptions and practices, which sometimes result into adverse health outcomes. Women having better knowledge regarding menstrual hygiene and safe practices are less vulnerable to reproductive tract infections and its consequences. The objective of the present study is to determine the factors affecting the existing practices of menstrual hygiene among the adolescent girls and to study the beliefs, conception and source of information regarding menstruation among the study population. Methods: A pre-tested semi-structured schedule containing information like socio-demographic factors, perceptions about menstruation, practice of menstrual hygiene, restrictions practiced during menstruation was administered to 200 adolescent girls by paying house to house visits. The data was entered in Microsoft Excel and analysed using Epi Info software version 7.2.3. Results: : Nearly three-fourths of the adolescent girls attained menarche before the age of 14 years and 87% had no knowledge about it prior to attaining menarche. Majority (86%) respondents use sanitary pads, while only 14 (7%) use new cloth pieces, 6 (3%) use reused cloth pieces. Except for attending school, many restrictions were imposed on them during menstruation including participation in religious activities, festivals, attending household chores, food restrictions, etc. Conclusions: Various cultural practices and ignorance are affecting the menstrual hygiene of the adolescent girls and they need to be educated in this regard.